MUSEUM DAN SEKOLAH: SINERGI KEBIJAKAN DEMOKRATISASI KEBUDAYAAN MELALUI PROGRAM PEMBELAJARAN SENI DAN BUDAYA DI KOTA LA ROCHELLE - PRANCIS - Wibowo, Agung; Winarsih, Dwi; Budiati, Atik Catur (UI Scholars Hub, 2024)
Our article describes the relationship between museums and schools as a policy of democratisation of French culture, a policy that has encouraged the ministry of education and the ministry of culture to work together in designing arts and culture learning programmes in museums and in schools. The case study of the implementation of the national policy of democratisation of culture by the municipality of La Rochelle is an important consideration that can help us to understand how the locality of public policy implementation in France can contribute specific characteristics to the cultural development and management of museums and schools. Arts and culture learning in museums aims to bring students into direct contact with museum collections. The aim is to give students real-life experiences, encouraging them to easily express or talk about them, both in the classroom and beyond. Learning in museums is designed to build sensitivity to emotions and impressions that arise when dealing directly with museum objects, looking at the shape, colour or material of museum objects. Students will comment and express their experiences. This is the virtue of the learning process.